Kemungkinan Penerapan Sistem Informasi Akuntansi Atas Aktivitas Penjualan Pada UMKM - Singgih Tiwut Atmojo (Jurnal Akuntansi dan Pajak, 2020)
The purpose of this study is to find out how Accounting Information Systems are applied to UMKM and how to apply Accounting Information Systems that are effective for UMKM. The form of research is a case study research with data collection techniques using observation, interviews and documentation. The results showed that UMKM had not yet implemented an effective and accurate system. The conclusions of this study are: 1. The control applied is still not effective, 2. The existence of negative findings: a. The absence of accurate records, b. Lack of control in the production and warehouse. There are no financial report. The advice given is that UMKM should improve the system that was previously implemented, the owners of UMKM carry out supervision that authorizes the segregation of duties for each employee, in order to avoid fraud.